THE THE EFFECT OF ADDING TOMATO EXTRACT (Solanum lycopersicum L.) to APPLE-BASED SHEET JAM (Malus sylvestris L.) AS AN ANTIOXIDANT - SARI, BINA LOHITA (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Antioxidants are substances that can prevent or reduce oxidative stress in physiological systems. The natural antioxidants found in our food are substances that can protect cells from the dangers of free radicals produced by the body's metabolism. Tomato (Solanum lycopersicum L.) and apple (Malus sylvestris L.) are natural compounds with strong antioxidant capacities which can be used in functional food. Both natural compounds will be made into jam sheets, a modified jam printed in sheet which is very easy to serve on bread and cakes. This research aimed to find the best formula of apple puree sheet jam added with differences of tomato juice concentration. There are 4 sheet jam formulas which are F1, F2, F3, and F4 use 100 g of apple puree and add tomato juice as 0 g, 60 g, 75 g, and 90 g respectively. The parameter test used for this research were hedonics test for panelists, water content test, pH value, total plate count, mold/yeast test, and antioxidant activity. The results showed that F4 was the best formula preferred by the panelists. The water content, pH value, total plate count, and mold/yeast test were 21.62%, 4.23, and 7.5 x102, respectively. The antioxidant activity value with an IC50 value of 87.14 ppm. The addition of 90 g of tomato juice on 100 g of apple puree produces sheet jam with strong antioxidant activity.